Precisão e trabalho escravo: uma análise das formas de trabalho análoga à escravidão no Estado do Maranhão - Lima, Hélio Araújo de (2023)
In recent years, Brazil has gone through serious economic and social crises, which have a direct impact on labor relations and, why not say, on the economy. Therefore, it has affected the worker's income, given the sharp drop in the offer of new jobs in the country. In this perspective, the article brought as an investigation problem a historical and contemporary rescue of occurrences related to work analogous to slavery. The present study seeks to demonstrate that it is not only the financial factors within the family that encourage the demand for this irregular practice. In some cases, it is verified the occurrence of work in conditions analogous to slavery, including in urban areas. There are even highlights that there are currently several demonstrations of work in these conditions, as the digital media invariably provides us with news of people who are rescued either at home, or in companies, or on farms. The research begins an analysis from the beginning, walks through the glamorization of slavery brought in our school benches, where they pass on information that since the enactment of the golden law, this type of offense to the dignity of the human person has not happened in Brazil, which remained demonstrated not be the expression of truth. After such notes, the possible causes for this continuity will be identified, as well as the current public policies that demonstrate its fight, with the main focus of not ending, at least mitigating the occurrences. The survey showed, based on official bodies, with the participation of society, that Maranhão is currently one of the largest exporters of labor analogous to slavery, whether due to socio-spatial issues, such as location, drought periods and even excessive rains or even, by the high rate of illiteracy. All this socio-spatial framework brought several concerns that motivated this research